2021
DOI: 10.1111/aogs.14166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surgeon and hospital volume for robot‐assisted and laparoscopic benign hysterectomy in Sweden

Abstract: Introduction:The study aims to analyze differences between robotic-assisted total laparoscopic hysterectomy (RATLH) and total laparoscopic hysterectomy (TLH) in benign indications, emphasizing surgeon and hospital volume.Material and methods: All women in Sweden undergoing a total hysterectomy on benign indications with or without a bilateral salpingo-oophorectomy from 1 January 2015 to 31 December 2017 (n=12 386) were identified from three national Swedish registers. Operative time, blood loss, conversion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…In contrast, some retrospective studies have stated that the operative time of RAH is shorter than that of TLH. 13,14 Moreover, some RCTs reported similar results. [7][8][9] Martínez-Maestre et al indicated that the TOT of RAH was shorter than that of TLH (p = 0.0001).…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, some retrospective studies have stated that the operative time of RAH is shorter than that of TLH. 13,14 Moreover, some RCTs reported similar results. [7][8][9] Martínez-Maestre et al indicated that the TOT of RAH was shorter than that of TLH (p = 0.0001).…”
Section: Discussionmentioning
confidence: 80%
“…Five studies of hysterectomy and one study combining all robotic gynaecology procedures were included; these studies demonstrated mixed results [19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Brunes et al did nd a signi cant relationship between surgeon volume and peri-operative outcomes, including blood loss and operative time [24]. Unger et al pooled all robotic gynaecological procedures in their analysis and demonstrated that higher surgeon volume was associated with reduced rates of conversion to an alternative procedure [20].…”
Section: Resultsmentioning
confidence: 99%
“…The use of high-precision instruments, excellent imaging of the anatomy, and good ergonomics mean that the risk of minimally invasive approaches requiring conversion in cases with advanced disease is decreasing and this approach can even be used in cases with complex constraints. Compared to open surgery, minimally invasive procedures reduce postoperative morbidity and require shorter hospital stays 7 8 9 10 11 , which can have a positive impact both economically and for the individual patient.…”
Section: Introductionmentioning
confidence: 99%
“…Durch Hochpräzisionsinstrumente, exzellente Darstellung der Anatomie und entlastende Ergonomie wird der minimalinvasive Zugang mit abnehmendem Risiko für eine Konversion auch bei fortgeschrittener Erkrankung und unter komplexen Randbedingungen nutzbar. Im Vergleich zur offenen Chirurgie führt dies wiederum zur Abnahme der postoperativen Morbidität und zu kürzeren Krankenhausverweildauern 7 8 9 10 11 , was sich sowohl volkswirtschaftlich als auch für das Individuum positiv auswirken kann.…”
Section: Introductionunclassified